Response to tocilizumab and work productivity in patients with rheumatoid arthritis: 2-year follow-up of FIRST ACT-SC study. Issue 1 (2nd January 2021) - Tanaka, Yoshiya; Kameda, Hideto; Saito, Kazuyoshi; Kaneko, Yuko; Tanaka, Eiichi; Yasuda, Shinsuke; Tamura, Naoto; Fujio, Keishi; Fujii, Takao; Kojima, Toshihisa; Anzai, Tatsuhiko; Hamada, Chikuma; et al.
Abstract: Objectives: We evaluated long-term control of rheumatoid arthritis (RA) in Japanese paid workers (PWs) and house workers (HWs) treated with subcutaneous tocilizumab (TCZ-SC) and explored factors affecting response to TCZ-SC regarding work productivity. Methods: This study collected data from patients with RA in the TCZ-SC +/− conventional synthetic disease-modifying antirheumatic drugs group. Factors affecting the response to tocilizumab regarding work productivity were explored using logistic regression. Differences in quality-adjusted life years (QALYs) between with/without response were analysed by a linear regression. Results: Data were analysed for 357/360 patients. Patients with a ≥ 75% improvement in activity impairment (AI) were considered responders. EuroQol-5 Dimension (EQ-5D), six-item Kessler psychological distress scale score (K6), Health Assessment Questionnaire Disability Index (HAQ-DI), and the patient's disease global health by visual analogue scale were significant contributors to TCZ-SC response based on improvements in AI. Work Functioning Impairment Scale, presenteeism, EQ-5D, K6, and HAQ-DI significantly contributed to the improvement of overall work impairment in PWs. Shorter disease duration also was related to TCZ-SC response based on AI improvements. Responders had significantly larger mean QALYs than non-responders (difference = 0.2614; p  < .001). Conclusions: These real-world clinical data support long-term work productivity control with TCZ-SC for biologic-naïve HWs and PWs with RA.